The Effect of Oxytocin Massage on Breastmilk Productioni in Postpartum Mothers at The Pratama Nining Clinic Lubuk Pakam Year 2023 - Sunengsih; Yessy Arisman; Silvina Dwi Yolanda (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Newborns do not need other intakes other than milk, but there are not a few postpartum mothers who give formula milk to their babies because of little or no ASI production, especially on the first day of the baby's birth. One of the causes of the low level of exclusive breastfeeding is the lack of the hormones oxytocin and prolactin, which play a very important role in the smooth production of milk. The purpose of this study was to determine the effect of oxytocin massage on increasing ASI production in postpartum mothers. This type of research is a pre-experimental study with One Group Pre and Post Test Design. The population in this study were 60 postpartum mothers during the last 3 months at the Pratama Nining Pelawati Clinic in 2023. The sample in this study was postpartum mothers with inclusion and exclusion criteria totaling 36 people. ASI production data was taken using a measuring cup which was then analyzed. Based on Shapiro Wilk's results, the average postpartum mother's ASI production before oxytocin massage was 24.78 while the average postpartum mother's milk production after oxytocin massage was 40.36. There is a significant effect of oxytocin massage on increasing ASI production with a p-value of 0.012 (p>0.05) It is recommended for health workers to be able to do oxytocin massage to increase ASI production in postpartum mother.